Extracellular histones aggravate autoimmune arthritis by lytic cell death - Jung, Jaeyong; Lee, Lucy Eunju; Kim, Hanna; Kim, Ji Eun; Jang, Sung Hoon; Roh, Jong Seong; Lee, Beomgu; Robinson, William H.; Sohn, Dong Hyun; Pyun, Jae-Chul; Song, Jason Jungsik (Frontiers in Immunology, 2022)
Although recent studies have demonstrated a proinflammatory effect of extracellular histones in sepsis via endothelial cytotoxicity, little is known about their contribution to autoimmune arthritis. Therefore, we investigated the role of extracellular histones in autoimmune arthritis and their cytotoxic effect on synoviocytes and macrophages. We measured histones in the synovial fluid of patients with rheumatoid arthritis (RA) and evaluated arthritis severity in a serum-transfer arthritis (STA) mouse model with intraperitoneal histone injection. Histone-induced cytotoxicity was measured using SYTOX green staining in the synoviocyte cell line MH7A and macrophages differentiated from the monocytic cell line THP-1, and the production of damage-associated molecular patterns (DAMPs) was measured by HMGB1 and ATP. Furthermore, we performed RNA-seq analysis of THP-1 cells stimulated with H2B-α1 peptide or with its citrullinated form. The levels of histones were elevated in RA synovial fluid, and histones aggravated arthritis in the STA model. Histones induced cytotoxicity and DAMP production in synoviocytes and macrophages. Chondroitin sulfate reduced histone-induced cytotoxicity, while lipopolysaccharides aggravated cytotoxicity. Moreover, the cytotoxicity decreased when the arginines in H2B-α1 were replaced with citrullines, which demonstrated its electrostatic nature. In transcriptome analysis, H2B-α1 changed the gene expression pattern of THP-1 cells involving chemokines, interleukin-1, -4, -10, -13, and toll-like receptor (TLR) signaling pathways. Extracellular histones were increased in RA synovial fluid and aggravated synovitis in STA. They induced lytic cell death through electrostatic interaction with synoviocytes and macrophages, leading to the secretion of DAMPs. These findings suggest that histones play a central role in autoimmune arthritis.